Principles of Functional Circuit Connectivity: Insights From Spontaneous Activity in the Zebrafish Optic Tectum - Marachlian, Emiliano; Avitan, Lilach; Goodhill, Geoffrey J.; Sumbre, Germán (Frontiers in Neural Circuits, 2018)
The brain is continuously active, even in the absence of external stimulation. In the optic tectum of the zebrafish larva, this spontaneous activity is spatially organized and reflects the circuit’s functional connectivity. The structure of the spontaneous activity displayed patterns associated with aspects of the larva’s preferences when engaging in complex visuo-motor behaviors, suggesting that the tectal circuit is adapted for the circuit’s functional role in detecting visual cues and generating adequate motor behaviors. Further studies in sensory deprived larvae suggest that the basic structure of the functional connectivity patterns emerges even in the absence of retinal inputs, but that its fine structure is affected by visual experience.